Distinct Properties of Human M-CSF and GM-CSF Monocyte-Derived Macrophages to Simulate Pathological Lung Conditions In Vitro: Application to Systemic and Inflammatory Disorders with Pulmonary Involvement - Lescoat, Alain (Int J Mol Sci, 2018)
Macrophages play a central role in the pathogenesis of inflammatory and fibrotic lung diseases. However, alveolar macrophages (AM) are poorly available in humans to perform in vitro studies due to a limited access to broncho-alveolar lavage (BAL). In this study, to identify the best alternative in vitro model for human AM, we compared the phenotype of AM obtained from BAL of patients suffering from three lung diseases (lung cancers, sarcoidosis and Systemic Sclerosis (SSc)-associated interstitial lung disease) to human blood monocyte-derived macrophages (MDMs) differentiated with M-CSF or GM-CSF. The expression of eight membrane markers was evaluated by flow cytometry. Globally, AM phenotype was closer to GM-CSF MDMs. However, the expression levels of CD163, CD169, CD204, CD64 and CD36 were significantly higher in SSc-ILD than in lung cancers. Considering the expression of CD204 and CD36, the phenotype of SSc-AM was closer to MDMs, from healthy donors or SSc patients, differentiated by M-CSF rather than GM-CSF. The comparative secretion of IL-6 by SSc-MDMs and SSc-AM is concordant with these phenotypic considerations. Altogether, these results support the M-CSF MDM model as a relevant in vitro alternative to simulate AM in fibrotic disorders such as SSc.